Encoding AIS Binary Messages in XML Format for Providing Hydrographic-related Information - Schwehr, Kurt; Alexander, Lee (The International Hydrographic Review, 2007)
A specification is proposed to enable hydrographic and maritime safety agencies to encode AIS messages using Extensible Markup Language (XML). It specifies the order, length, and type of fields contained in ITU-R.M.1371-1. A XML schema validates the message definitions, and a XSLT style sheet produces reference documentation in ’html’ format. AIS binary messages in XML are an effective means to communicate dynamic and real-time port/waterway information. For example, tidal information can be continuously broadcast to maritime users and applied to a "tide-aware" ENC. The XML format aligns with the type of data encapsulation planned for the IHO Geospatial Standard for Digital Hydrographic Data (S-100).